Filogenia, biogeografia e revisão taxonômica de Chamaecrista Sect. Absus subsect. Absus Ser. Rigidulae (Leguminosae, Caesalpinioideae) - Souza, Alessandro Oliveira de (2016)
Leguminosae is the third largest family of plants, encompassing about 751 genera and 19,500 species distributed in the subfamilies Caesalpinioideae, Mimosoideae, and Papilionoideae. In its current circumscription, Caesalpinioideae comprises about 171 genera and 2,250 species Chamaecrista, the largest genus, has about 340 species (257 in Brazil, from which 208 are endemic) with Pantropical distribution and is subdivided into six sections, among which Absus is the richest, with about 180 species distributed in the subsections Absus, Adenophyllum, Baseophyllum, and Otophyllum. The subsection Absus comprises 31 series, among which Rigidulae, with 24 Brazilian species, stands out due to the conserved floral morphology and diverse aspects of growth, and also because it is paraphyletic and has not been revised since 1982. In this dissertation we aimed to reconstruct the historical evolution of Chamaecrista ser. Rigidulae and review the taxonomy of its species applying usual techniques in taxonomy and molecular phylogeny. The results are presented as seven articles standardized according to the journals where they have already been or will be published. The first article presents the phylogeny and biogeography of Chamaecrista ser. Rigidulae based on the regions trnL-F and trnE-T (cpDNA) and ITS (nrDNA), the polyphyletism of the group, and its redefinition to a monophyletic group herein called Clade Rigidulae after the exclusion of C. brachyblepharis and C. ciliolata and the inclusion of C. botryoides and C. sincorana. This clade originated 5My in the Highlands of Central Brazil, diversified into two main lineages, one on the Espinhaço Range (4.27 My) and the other on the Highlands of Goiás (4.17 My), and has flowers with the posterior petal similar to a banner and leaves with divaricate leaflets as synapomorphies. The second article is about a taxonomic revision of the series Rigidulae, for which 30 species have been recognized, five of them new to science (C. floribunda, C. irwiniana, C. sparsifolia, C. tenuicaulis, and C. elata sp. nov. unpublished), one new status (C. obolaria ≡ C. chaetostegia var. obolaria), four lectotypifications, three new records (one in Bahia and two in Minas Gerais), illustrations and photographs of some species, maps showing the geographic distribution, and comments about taxonomy their conservation status. Regarding the five other articles, four have already been published and present descriptions of new species or taxonomic adjustments in the genus, whereas the last one, not published yet, has the same scope. The results of this research revealed the evolutionary and biogeographic history of the series Rigidulae, as well as its richness and corroborate the diversity and endemism of Chamaecrista in the Cerrado Biome.